To evaluate the effects of Nd:YAG laser posterior capsulotomy on best corrected visual acuity (bcva) and intraocular pressure - Patel, Ohm Vrajlal; Chandrakar, Neha; Bajaj, Piyush; Mahajan, Sonam (Asian Journal of Medical Sciences, 2017)
Background: Nd:YAG laser is non-invasive and effective means to deal with the posterior capsule opacification.However safe it may have some inherent complications. Rise of intraocular pressure is frequently encountered and incompletely understood complication of YAG laser capsulotomy and documented with conflicting results. Aims and Objective: To assess the efficacy of Nd: YAG laser capsulotomy in term of visual outcome(Best Corrected Visual Acuity) and also study the changes in IOP after the procedure. Materials and Methods: Study evaluated the changes in IOP and visual acuity after Nd-YAG laser capsulotomy in 100 eyes with significant PCO after uncomplicated cataract surgery with IOL implantation. Complete ocular examination including visual acuity, anterior segment examination with slit lamp, fundus and applanation tonometry were performed pre and post-laser in all cases. Posterior capsulotomy was done with VISULAS YAG III Q-switched Nd: YAG laser machine by ZEISS. IOP was recorded before and then at 1hour, 1 Day, 1 week and 1 month post-laser in order to determine the IOP changes. Results: Pre-laser visual acuity ranged from 1/60 to 6/12. Results showed statistically significant improvement in BCVA with 70% patients had BCVA 6/6, 21% had BCVA 6/9 and 8% having BCVA 6/12 post-laser at 1 month. It was observed that 36% of the patients showed no change in IOP while 64% patients showed elevated IOP. Among these 59% patients show rise in IOP that was ≤5 mm Hg while only 5% of the patients had a rise of more than IOP >5 mm Hg. Most of these patients achieved their baseline IOP within 1 day and only 7 % patient had rise in IOP compared to baseline IOP on day 1. None of the patients show elevated IOP after 1 week. Conclusion: Our study showed that Nd: YAG laser posterior capsulotomy provided excellent results in terms of visual improvement and most of the patients had a rise of <5mm Hg which was transient in nature and routine antiglaucoma medication may not be needed in all the patient undergoing Nd;Yag capsulotomy, however caution should be exercised in glaucomatous, aphakic, high myopic and other high risk patients. Asian Journal of Medical Sciences Vol.8(5) 2017 93-97